Sox7 is an independent checkpoint for β-catenin function in prostate and colon epithelial cells - Guo, Lizheng (2008)
The presence of somatic β-catenin mutations in some prostate cancers implies that aberrant WNT signaling is involved in the cancer’s development. Although β-catenin stability is regulated by a multi-component destruction complex, mutational alterations of β-catenin or other components of the destruction complexes are rare in prostate tumors. Therefore, β-catenin may be regulated by another protein in the prostate. In fact, recent linkage and somatic deletion analyses in prostate cancers reveal a 1.4 Mb candidate tumor suppressor locus on 8p23.1, which includes the Sox7 gene. Here we show that Sox7 protein expression was indeed down-regulated in 47% (15/32) of prostate adenocarcinomas. Also, Sox7 mRNA was down-regulated in 60% of snap-frozen tumors. This down-regulation was found to be due to tumor-specific promoter hypermethylation, which was present in 48% (10/21) of primary prostate tumors and 44% (11/25) of prostate cancer cell lines/xenografts. We discovered that Sox7 protein physically interacts with β-catenin and suppresses β-catenin-mediated transcription by depleting active β-catenin. Furthermore, in HCT116 colorectal cancer cell lines with Sox7 inactivation, ectopic Sox7 expression suppressed cell proliferation and inhibited transcription that was activated by an endogenous mutant β-catenin. Even though nearly all colorectal cancers contain mutations in β-catenin or APC/Axin, epigenetic silencing of Sox7 was still observed. These data suggest that Sox7 is a tumor suppressor that functions as an independent checkpoint for β-catenin transcriptional activity. Inactivation of Sox7 could promote the development of a majority of colorectal tumors and approximately half of prostate tumors.